Toot - Patricelli, Leslie (Somerville, Massachusetts : Candlewick Press, 2014)
A baby is delighted to experience his very first fart.
Cover title.
Preschool
Keywords: Board books; Babies -- Fiction; Flatulence -- Fiction; Board books